Self-defeat and its relationship to sychological adjustment among students of the College of Education for Human Sciences - Salih Ali, Assist.Prof. Asmaa; Farhan Rayyis, Assist. Lect. Ahmed (Basra studies journal, 2023)
The current research aims to identify the relationship between self-defeat and psychological adjustment among students of College of Education for Human Sciences, as the study sample consisted of (130) male and female students (87) males and (43) females. The researchers used the scale of (AlAsimi 2013) for measuring self-defeat and a scale of (Al-Khatem secret, 2017) to measure psychological compatibility. The results of the study showed the following: 1- There are no indicators of self-defeat among students of College of Education for Human Sciences. 2- Students of College of Education for Human Sciences enjoy psychological compatibility. 3- There are statistically significant differences in favor of males in the self-defeat variable, while there are no statistically significant differences due to the age stage variable, in addition to the presence of statistically significant differences in favor of the study stage. 4- There are statistically significant differences in favor of males in the psychological adjustment variable, while there are no statistically significant differences due to the variables of the age stage and the educational stage 5- There is a statistically significant relationship between self-defeat and psychological adjustment among students of College of Education for Human Sciences.